The Mediating Role of Cognitive Processing in the Relationship Between Negative and Positive Effects of Trauma Among Female Victims of Domestic Violence - Ogińska-Bulik, Nina (Journal of interpersonal violence, 2021)
Exposure to domestic violence may lead not only to negative but also positive consequences of trauma. Negative effects are indicated by posttraumatic stress symptoms (PTSSs), and positive effects by posttraumatic growth (PTG) changes. PTG has been conceptualized to follow experiences of PTSSs. Therefore, the positive and negative effects of trauma appear to be related to one another. The cognitive processing may play a special role in determining whether the positive and negative consequences of trauma exposure are experienced. The aim of the study was to establish the mediating role of multiple patterns of cognitive processing, reflected by the cognitive strategies used to cope with trauma, in the relationship between negative and positive posttraumatic changes in women following domestic violence. Data were obtained from 63 Polish women who had experienced domestic violence. The age of the respondents ranged from 19 to 71 years (M = 42.25, SD = 14.81). The Polish versions of the following standardized tools were used: the Posttraumatic Stress Disorder Checklist (PCL-5), the Posttraumatic Growth Inventory (PTGI), and the Cognitive Processing of Trauma Scale (CPOTS). PTSS severity appeared to be negatively related to that of PTG. Negative coping strategies were positively related to the PTSS severity but negatively to PTG, while positive strategies were negatively related to the PTSS severity but positively to PTG. Cognitive strategies for coping with trauma, such as resolution/acceptance, downward comparison, and regret, appeared to play a mediating role in the relationship between PTSS severity and PTG. Positive coping strategies strengthen the occurrence of positive posttraumatic changes while strategy of regret weakens the PTG changes occurrence. The process of adaptation and human development among people who have experienced traumatic events is favored by the use of more frequent positive and less frequent negative strategies of dealing with trauma.